Why Turkish students prefer to attend to vocational schools - (:unkn) unknown (My University, 2011)
Production is an indispensably important part of a country's economy, and to realise high quality production a country needs high quality manpower. In Turkey, the main function of vocational high schools is to prepare workforce for the local industries. The purpose of this study was to investigate the factors affecting students' decisions to enter vocational high schools. A nonparametric statistical method was used for analysis. The results from the data analysis showed that socioeconomic background was a main factor for students' choice of vocational high school. Other factors include young peoples' personal preference, and their parents' decision to choose vocational high schools. © EuroJournals Publishing, Inc. 2011.
Keywords: And Chi square analysis; Nonparametric statistical method; Turkey; Vocational high school